Estimates of the energy deficit required to reverse the trend in childhood obesity in Australian schoolchildren. (11th November 2015) - Cochrane, Thomas; Davey, Rachel; de Castella, F. Robert
Abstract: Objectives: To estimate: 1) daily energy deficit required to reduce the weight of overweight children to within normal range; 2) time required to reach normal weight for a proposed achievable (small) target energy deficit of 0.42 MJ/day; 3) impact that such an effect may have on prevalence of childhood overweight. Methods: Body mass index and fitness were measured in 31, 424 Australian school children aged between 4.5 and 15 years. The daily energy deficit required to reduce weight to within normal range for the 7, 747 (24.7%) overweight children was estimated. Further, for a proposed achievable target energy deficit of 0.42 MJ/day, the time required to reach normal weight was estimated. Results: About 18% of children were overweight and 6.6% obese; 69% were either sedentary or light active. If an energy deficit of 0.42 MJ/day could be achieved, 60% of overweight children would reach normal weight and the current prevalence of overweight of 24.7% (24.2%–25.1%) would be reduced to 9.2% (8.9%–9.6%) within about 15 months. Conclusions: The prevalence of overweight in Australian school children could be reduced significantly within one year if even a small daily energy deficit could be achieved by children currently classified as overweight or obese.